Membandingkan Model Pembelajaran Snowball Throwing dan Jigsaw Terhadap Hasil Belajar IPA Kelas V SD - Kurniawan, Fika Habib; Bintartik, Lilik; Surayanah, Surayanah (Jurnal Ilmiah Pendidikan Dasar, 2024)
Science learning is currently considered less interesting so students are less enthusiastic about participating in learning and this affects their learning outcomes. This research aims to compare the cognitive learning outcomes of students who use the Snowball Throwing and Jigsaw learning models. The research used quasi-experimental, non-equivalent control group design. The research was carried out at SDN Kayen Kidul in class V with 32 students divided into 2 groups. This research took samples using saturated sampling techniques. Research data was obtained through test instruments. The data was then analyzed using the Independent Sample T Test and the N Gain Score Test. Based on the Independent Sample T-Test, the significance value was 0.512, meaning that there was no significant difference in the learning outcomes of students who used the Snowball Throwing and Jigsaw models. Based on the N Gain Score test, it is known that the Snowball Throwing model is more effective than the Jigsaw model, because the N Gain Score value for the Snowball Throwing class is greater than 0.6465, compared to the value for the Jigsaw class 0.5835. Based on the two test results above, it is known that the Snowball Throwing learning model is more effective in influencing student learning outcomes compared to the Jigsaw learning model on the main subject of human blood circulation in elementary schools, as well as being a novelty in this research. The results of this research can serve as guidance and recommendations in developing strategies or policies in relevant fields.